PERAN KOMISI YUDISIAL DALAM SISTEM KETATANEGARAAN INDONESIA - Bahar, Ujang (DERECHTSSTAAT, 2017)
The Judicial Commission (JC) is a new independent state institution established as a product of the reform in the constitutional system and its existence is confirmed in the 1945 Constitution. The Judicial Commission was established following the idea of a one-roof system in the judicial authority. Among the roles and authority of the Judicial Commission are to propose appointment of the Supreme Court justices to the House of Representatives (DPR) and to supervise the conducts of justices/judges in order to maintain their respect, dignity and honor and good conduct.Â  However, in the performance of its duties, the Judicial Commission is not yet as independent as it has been expected. It can be seen from its limited authority. In supervising the conduct of the judges/justices, the Commission is not authorized to impose any sanctions and in the process of selection of candidates for the Supreme Court justices, its authority is limited only at the ratio 3:1. Therefore, the existence of the Commission under the 1945 Constitution becomes unclear, since it is placed under the chapter of the judicial authority, but in reality it does not exercise its judicial authority and only functions as a supervisory agency like the State Audit Board (BPK) instead. Consequently, the Commission only serves as the supporting institution to the Supreme Court, President and the House of Representatives. In order that the Commission becomes truly independent as an institution which supervises the implementation of the judicial power sitting at an equal level with other state institutions, it is necessary to strengthen the institution by making amendments (to re-determine the position of the Judicial Commission) in the 1945 Constitution and other relevant laws and regulations.